2018
DOI: 10.25267/rev_eureka_ensen_divulg_cienc.2018.v15.i3.3605
|View full text |Cite
|
Sign up to set email alerts
|

Comparación entre la realización de maquetas y la visualización para mejorar la alfabetización visual en anatomía humana en futuros docentes

Abstract: Resumen: La alfabetización visual es esencial para la formación docente en ciencias, especialmente en anatomía humana, cuya enseñanza y aprendizaje están apoyados en el uso de gráficos y requiere la adquisición de una visión espacial del cuerpo humano. Sin embargo, ha sido poco estudiada en maestros de Primaria y no existen investigaciones que evalúen la efectividad de métodos que permitan mejorarla. El presente trabajo, llevado a cabo con 194 maestros en su último año de formación, además de hacer un diagnóst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Otros proyectos utilizan impresiones 3D de diferentes regiones anatómicas, diferenciando cada una de sus partes por medio de colores, lo que facilita la identificación y el entendimiento de la relación entre las estructuras que las conforman 17 . También, se encuentran propuestas de enseñanza que utilizan la elaboración de maquetas para lograr la alfabetización visual y la ubicación espacial, lo cual se evalúa por medio de la elaboración de dibujos de cortes transversales de regiones corporales; estos cortes son los de mayor dificultad de comprensión 18 .…”
Section: Discussionunclassified
“…Otros proyectos utilizan impresiones 3D de diferentes regiones anatómicas, diferenciando cada una de sus partes por medio de colores, lo que facilita la identificación y el entendimiento de la relación entre las estructuras que las conforman 17 . También, se encuentran propuestas de enseñanza que utilizan la elaboración de maquetas para lograr la alfabetización visual y la ubicación espacial, lo cual se evalúa por medio de la elaboración de dibujos de cortes transversales de regiones corporales; estos cortes son los de mayor dificultad de comprensión 18 .…”
Section: Discussionunclassified
“…Regarding the learning of science, physical model-based modelling promotes not only the learning of the elements and the structure where they are located, but also the related relationships and processes (Steer et al 2005;García and Mateos 2018); that is, they link structure to processes, a common difficulty in, for example, the understanding of nutrition or plate tectonics. Interestingly, Gómez (2008) found that physical models specifically contributed to the learning process, facilitating students to build the model of human senses.…”
Section: The Use Of Physical Models In Science Educationmentioning
confidence: 99%
“…However, fewer studies aim to assess the effectiveness of teaching proposals that may promote conceptual change on this topic. For that purpose, different strategies such as experiments simulating processes (Bahamonde and Gómez Galindo 2016;Mattos Feijó, de Andrade and Coutinho-Silva, 2020), virtual strategies (Šorgo, Hajdinjak, and Briški 2008;Vilkonienė 2009) and physical models (Bahamonde and Gómez Galindo 2016;García and Mateos 2018) have been proposed. The use of a dramatic simulation was also proposed (Benarroch 2008) but it was more focused on nutrition than on the DS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also teaching-learning proposals that use the elaboration of models to achieve visual literacy and spatial location evaluated through the elaboration of crosssectional drawings of body regions, which are the most difficult to understand (García Fernández & Mateos Jiménez, 2018). The University of California facilitates learning by metaphors, analogies and facial expressions to provide new ways of thinking, focus activities on common human functions and improve understanding of anatomical and physiological relationships.…”
Section: Cluster Of Teaching-learning Through Variousmentioning
confidence: 99%